Penerapan Model Pembelajaran Picture and Picture dengan Media Power Point untuk Meningkatkan Hasil Belajar Pendidikan Agama Kristen Tentang Penciptaan Pada Siswa Kelas 3 SD Gmim Koha Kecamatan Mandolang Minahasa - Rame, Thofan; Supit, Sugijanti (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The application of the picture and picture learning model using power point media can improve Christian Religious Education learning outcomes for grade 3 students at GMIM Koha Elementary School, Mandolang Minahasa District. The research was conducted on grade 3 students at SD GMIM Koha consisting of 8 male students and 12 female students with a total of 20 students. This research was carried out from September to October 2023. The method used a classroom action research design with the stages of Planning, Action Implementation, Observation and Reflection. The data was analyzed using the completeness of learning outcomes technique with the formula KB  The results of the research show that the application of the picture and picture learning model using power point media can improve learning outcomes in Christian Religious Education about Creation from cycle I to cycle II for students at GMIM Koha Elementary School, Mandolang District, Minahasa.